Synthesis of Algorithm to Change Guidance Law for Air-to-Air Missiles Intercept Separating Targets (Advances in Military Technology, 2023)
This paper presents the results of summarizing the algorithm of target selection and changing guidance law applied for medium and long-range air-to-air intercept missiles to ensure the ability to detect and distinguish the group-separating target, which in turn improving the efficiency in tracking and terminating the selected targets. The proposed algorithm reduces the miss distance to a minimal value while ensuring two primary requirements, including distinguishing each target in the group by Doppler frequency and identifying the flight direction of the target to track and destroy.
Keywords: algorithm of choosing optimal guidance laws; separating target; supermaneuverable target; optimal proportional pre-emptive navigation law